TAX AMNESTY, CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK - Cindy Muljadi; Maria Eugenia Hastuti; Hari Hananto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
Some elements of this research are important elements in the company, but also become one of the elements of the company to do tax avoidance. This study aims to prove empirically the effect of tax amnesty, Corporate Social Responsibility (CSR), and Good Corporate Governance (GCG) on tax avoidance by companies. The data in this study used a sample of all non-financial sector companies that have been listed on the IDX with a total sample of 591 companies for 3 years, selected using purposive sampling technique. The hypothesis that was tested using multiple linear regression models. The results showed that the tax amnesty had a positive and significant effect on tax avoidance. CSR has a positive and significant effect on tax avoidance. Meanwhile, GCG which is proxied by independent commissioners and audit committee has a negative and significant effect on tax avoidance.